2007
DOI: 10.1038/sj.ejcn.1602931
|View full text |Cite
|
Sign up to set email alerts
|

Migration and differences in dietary habits—a cross sectional study of Finnish twins in Sweden

Abstract: Objective: To compare dietary habits between Finnish twin migrants to Sweden and their co-twins always living in Finland, and to analyse how migration influenced food consumption patterns in the migrants. Subjects/Methods: Same-sexed twin pairs born in Finland below 75 years of age, with at least one twin migrating to Sweden (n ¼ 1083 pairs). Dietary habits were assessed by a food frequency questionnaire included in a comprehensive mailed questionnaire (response rate 71%). For 76 male twin pairs, information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“…The Chinese study found higher sodium intake in migrants than rural participants, which was also seen in a migration study in Kenya [18]. International migration studies have found varied effects of migration on diet [19][30], often from a traditional to more western style of diet.…”
Section: Introductionmentioning
confidence: 67%
“…The Chinese study found higher sodium intake in migrants than rural participants, which was also seen in a migration study in Kenya [18]. International migration studies have found varied effects of migration on diet [19][30], often from a traditional to more western style of diet.…”
Section: Introductionmentioning
confidence: 67%
“…The fourth Swedish study was performed on same-sexed twin pairs born in Finland (<75 years), with at least one twin migrating to Sweden ( N =1,083 twin pairs). Dietary habits were assessed by a FFQ (response rate 71%), and in a subgroup of 76 male twin pairs also by a dietary history covering the previous year (49). Migrants in Sweden had a lower intake of typical Finnish foods like dark rye bread and berries, and an increased consumption of fresh food compared to co-twins living in Finland.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Turkish/Moroccan children skipped breakfast more often than children of Dutch origin (7) . As shown in a recent twin study, even migration from Finland to Sweden was significantly associated with changes in dietary pattern (8) . The aim of the present study was to determine the specific food intake of children and adolescents living in Germany with different migrant status from a representative sample.…”
mentioning
confidence: 91%